Highly effective anti-corrosion epoxy spray coatings containing self-assembled clay in smectic order. Issue 6 (18th December 2014) - Li, Peng; He, Xingliang; Huang, Tsao-Cheng; White, Kevin L.; Zhang, Xi; Liang, Hong; Nishimura, Riichi; Sue, Hung-Jue
Abstract : Epoxy nanocomposite coatings containing self-assembled α-zirconium phosphate nanoplatelets (ZrP) in smectic order were successfully prepared by spray-coating on an aluminum substrate using a simple, energy-efficient fabrication process that is suitable for industrial practices. Abstract : Epoxy nanocomposite coatings containing self-assembled α-zirconium phosphate nanoplatelets (ZrP) in smectic order were successfully prepared by spray-coating on an aluminum substrate using a simple, energy-efficient fabrication process that is suitable for industrial practices. Aluminium substrates with smectic epoxy/ZrP coatings showed a substantial improvement in corrosion resistance compared to the metal surface coating with unfilled epoxy alone. Lyotropic liquid crystal behaviour of ZrP nanoplatelets was observed in a number of different solvents, which suggests the phenomena are largely entropically driven and would be suitable for various coating systems. The results show that the epoxy coatings containing highly aligned ZrP nanoplatelets in smectic order may be used to effectively protect metal surfaces from corrosion using a scalable and simple approach.